Safety of low dose heparin in elective coronary angioplasty. Issue 6 (June 1997) - Koch, K. T.; Piek, J. J.; de Winter, R. J.; David, G. K.; Mulder, K.; Tijssen, J. G.; Lie, K. I.
Abstract : OBJECTIVES: To evaluate the safety of a low dose of heparin in consecutive stable patients undergoing elective percutaneous transluminal coronary angioplasty (PTCA). DESIGN: Open prospective study in a single centre. PATIENTS: 1375 consecutive patients had elective PTCA (1952 lesions: type A 11%, B1 34%, B2 36%, and C 19%). There were no angiographic exclusion criteria. INTERVENTIONS: A bolus of 5000 IU heparin was used as the standard anticoagulation regimen during PTCA. The sheaths were removed immediately after successful completion of the procedure. Prolongation of heparin treatment was left to the operator's discretion. MAIN OUTCOME MEASURES: Procedural success was defined as < 50% residual stenosis without death from any cause, acute myocardial infarction, urgent coronary bypass surgery, or repeat angioplasty within 48 hours for acute recurrent ischaemia; the need for prolonged heparinisation; and the occurrence of puncture site complications. RESULTS: Procedural success without clinical events was achieved in 90% of patients. Mortality was 0.3%; coronary bypass surgery was performed in 1.7% of the procedures. The rate of myocardial infarction was 3.3%; repeat angioplasty within 48 hours was carried out in 0.7% of patients. A total of 89.1% of the patients were treated according to the protocol. Prolonged treatment with heparin was considered necessary in 123 patients (8.9%). Repeat angioplasty for abrupt closure was performed in two patients shortly after sheath removal and in two during prolonged heparinisation. Puncture site complications occurred in 2.1% of patients (low dose heparin 1.9% and prolonged heparinisation 4.9%). CONCLUSION: Elective PTCA can be safely performed using a low dose of heparin, with a negligible risk for subacute closure. Low dose heparin may reduce the incidence of puncture site complications, shorten hospitalisation, and enable out-patient angioplasty.